The Organization of the Primate Insular Cortex - Evrard, Henry C. (Frontiers in Neuroanatomy, 2019)
Long perceived as a primitive and poorly differentiated brain structure, the primate insular cortex recently emerged as a highly evolved, organized and richly connected cortical hub interfacing bodily states with sensorimotor, environmental, and limbic activities. This insular interface likely substantiates emotional embodiment and has the potential to have a key role in the interoceptive shaping of cognitive processes, including perceptual awareness. In this review, we present a novel working model of the insular cortex, based on an accumulation of neuroanatomical and functional evidence obtained essentially in the macaque monkey. This model proposes that interoceptive afferents that represent the ongoing physiological status of all the organs of the body are first being received in the granular dorsal fundus of the insula or “primary interoceptive cortex,” then processed through a series of dysgranular poly-modal “insular stripes,” and finally integrated in anterior agranular areas that serve as an additional sensory platform for visceral functions and as an output stage for efferent autonomic regulation. One of the agranular areas hosts the specialized von Economo and Fork neurons, which could provide a decisive evolutionary advantage for the role of the anterior insula in the autonomic and emotional binding inherent to subjective awareness.